Valuation of pemphigus vulgaris and pemphigus foliaceus health states: a convenience sample experiment. (8th August 2016) - Rencz, F.; Brodszky, V.; Stalmeier, P.F.M.; Tamási, B.; Kárpáti, S.; Péntek, M.; Baji, P.; Mitev, A.Z.; Gulácsi, L.
Summary: Background: Health‐related quality of life (HRQoL) in pemphigus has been widely investigated; nevertheless, utility values for economic evaluations are still lacking. Objectives: To estimate health utilities for hypothetical pemphigus vulgaris (PV) and pemphigus foliaceus (PF) health states in a general population sample. Methods: Three health states (uncontrolled PV, uncontrolled PF and controlled pemphigus) were developed based on a systematic literature review of HRQoL studies in pemphigus. Utilities were obtained from a convenience sample of 108 adults using a visual analogue scale (VAS) and 10‐year time trade‐off (TTO). Lead‐time TTO was applied for health states regarded as worse than dead with a lead time to disease time ratio of 1 : 1. Results: The mean VAS utility scores for PV, PF and controlled pemphigus were 0·25 ± 0·15, 0·37 ± 0·17 and 0·63 ± 0·16, respectively. Corresponding TTO utilities were as follows: 0·34 ± 0·38, 0·51 ± 0·32 and 0·75 ± 0·31. Overall, 14% and 6% judged PV and PF as being worse than dead. For both VAS and TTO values, significant differences were observed between all health states ( P < 0·001). VAS utilities were rated significantly lower compared with TTO in each health state ( P < 0·001). Conclusions: This is the first study that reports health utility values for PV and PF. Successful treatment of pemphigus might result in significant utility gain (0·24–0·41). These empirical findings with respect to three health states in pemphigus may serve as anchor points for further utility studies and cost‐effectiveness analyses. Abstract : What's already known about this topic? Patients with pemphigus have a substantially impaired quality of life. What does this study add? This is the first study using a preference‐based outcome measure to provide health utility values for pemphigus. Successful treatment of pemphigus might result in significant utility gain. Utilities for both uncontrolled pemphigus vulgaris and pemphigus foliaceus were valued more severe than for uncontrolled atopic dermatitis or psoriasis in other studies. Our utilities can be used as a guide for future utility studies and cost‐effectiveness analyses.